2006
DOI: 10.14411/fp.2006.023
|View full text |Cite
|
Sign up to set email alerts
|

Fish-isolated Naegleria strains and their phylogeny inferred from ITS and SSU rDNA sequences

Abstract: Abstract. Effort was made to identify Naegleria strains isolated from organs of fish, using phylogenetic analyses of SSU rDNA and ITS sequences. Eighteen fish-isolated strains studied enlarged substantially the so far available set of Naegleria strains characterized by both molecular markers. The phylogenetic analyses of separate and concatenated SSU rDNA and ITS sequences revealed phylogenetic relationships of strains under study; however, they failed to solve classification of fish-isolated strains into spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…of SSU rDNA sequences deposited in GenBank are summarized in Table 1. The Naegleria strain (GERK) isolated from rainbow trout sampled in farm K (from a fish with histologically proven infection with amoeba trophozoites) was found to be closely related to Naegleria strains isolated previously from gills of roach Rutilus rutilus (L.) and skin of wels catfish Silurus glanis L. (Dyková et al 2006). The generic diagnosis of the isolated amoeba strains revealed a broad spectrum of possible agents of gill lesions, but did not allow relating them to amoebae found in histological material.…”
Section: Amoebae Isolated From Ngd-affected Gillsmentioning
confidence: 82%
“…of SSU rDNA sequences deposited in GenBank are summarized in Table 1. The Naegleria strain (GERK) isolated from rainbow trout sampled in farm K (from a fish with histologically proven infection with amoeba trophozoites) was found to be closely related to Naegleria strains isolated previously from gills of roach Rutilus rutilus (L.) and skin of wels catfish Silurus glanis L. (Dyková et al 2006). The generic diagnosis of the isolated amoeba strains revealed a broad spectrum of possible agents of gill lesions, but did not allow relating them to amoebae found in histological material.…”
Section: Amoebae Isolated From Ngd-affected Gillsmentioning
confidence: 82%
“…The phylogenetic reconstruction of the SSU rDNA sequence data using methods of maximum parsimony (MP), maximum likelihood (ML) and Bayesian inference (BI) followed the practice applied in previous studies (Dyková et al 2005a(Dyková et al , 2006. MP (heuristic search with three bisection-reconnection branch swapping; gaps as missing data; transition/transversion (Ts:Tv) ratio=1:2; bootstrap statistical support with 1 000 replications) and ML (GTR+I+Γ model of evolution; bootstrap statistical support with 500 replications) analyses were performed in the program package PAUP* version 4.0b10 (Swofford 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Heteroloboseans were found also in the gut of animals (e.g., Tetramitus spp., Paravahlkampfia ustiana, Percolomonas sulcatus) and gills, skin, and internal organs of fish (Naegleria spp.) (e.g., Brugerolle & Simpson, 2004;Dyková et al, 2001Dyková et al, , 2006Schuster et al, 2003).…”
Section: Ecology Of Heteroloboseamentioning
confidence: 99%
“…Despite strains of Naegleria fowleri are even more variable, they are considered to be conspecific instead of belonging to several different species (De Jonckheere, 2004, 2011. Dyková et al (2006) even showed that there exists an intragenomic polymorphism in Naegleria clarki. All these examples show that the ITS region should be no longer used for new species descriptions until the problem of species concept and intraspecific polymorphism within Heterolobosea is settled.…”
Section: Species Concept Of Heteroloboseamentioning
confidence: 99%